Reliability Analysis of In-person and Virtual Goniometric Measurements of the Upper Extremity - Tracy Spigelman; Leah Simpkins; Casey Humphrey; Yehor Vitel; Aaron Sciascia (International Journal of Sports Physical Therapy)
# Background